Cost of capital and discount rates in cash flow valuations for resources projects - Lilford, Eric; Maybee, Bryan; Packey, Daniel J. (Pergamon Press, 2018)
© 2018 Elsevier Ltd The discounted cash flow valuation methodology calculating the net present value, and derivatives of this methodology, rely on the use of discount rates to arrive at a value. Generally, a single discount rate is used over the life of the resources project. Where discounting factors using more than one discount rate are used, these factors seldom incorporate the impacts of changing debt to equity ratios, increasing capitalization of projects, equity returns trending towards the risk free rate and finally a defendable premium incorporated to reflect technical risk. This paper provides a discussion and solutions to these issues and gives the reader simple yet defendable tools to reconsider what, why and how discount rates should be used.